The QuillBot grammar checker: friend or foe of ESL student writers? / Ho Chui Chui - Ho, Chui Chui (Universiti Teknologi MARA, Kedah, 2022)
The use of automated written corrective feedback applications in the writing classroom has been widely researched. However, as the QuillBot grammar checker was newly launched, no studies had been conducted on its accuracy and usability among English as a Second Language (ESL) student writers. To address this gap, a small-scale sentence- and paragraph-level test was carried out to determine whether it would be a useful tool for ESL students to obtain feedback in real-time instead of waiting for teacher corrective feedback. The new, freely available grammar checker was tested along with the free version of two other popular grammar checking tools, Grammarly and Ginger. Actual writing samples from second-year diploma students were used. The results indicate that the QuillBot grammar checker outperformed the other two software. However, this tool is not perfect and users will still have to manually check for undetected errors and decide if suggestions should be accepted or ignored. Therefore, it is recommended that QuillBot should be used to supplement and not replace teacher feedback. With students using the QuillBot grammar checker in their writing tasks, teachers do not only save time on checking language errors but also have more time to provide feedback regarding global writing concerns, namely, content and organization.